Financial Innovation and Sharia Governance: An Empirical Study of Cryptocurrencies and Traditional Banking Risk–Return Dynamics in Indonesia - Rasyid, Abdul; Zatnika, Yudi (Al Urwah : Sharia Economics Journal, 2025)
This study investigates the risk–return dynamics of Bitcoin and Ethereum compared with traditional fixed-term bank deposits in Indonesia between 2020 and 2024. Using historical daily price data and interest rates, the research calculates annualized returns, volatility, and Sharpe Ratios to assess performance. Results show that cryptocurrencies offer extraordinary potential returns during bullish cycles but also suffer severe downturns, making them suitable only for high-risk, long-term investors. Bank deposits, in contrast, provide stable yet modest returns, reinforced by Indonesia Deposit Insurance Corporation (LPS) guarantees. From a Sharia perspective, bank deposits are problematic due to their riba-based structure, while cryptocurrencies raise concerns over gharar and maysir. The study highlights the rise of Sharia-compliant alternatives such as sukuk and gold-backed digital currencies as ethical solutions. The contribution lies in bridging financial economics with Islamic governance by comparing conventional, digital, and Sharia instruments in the Indonesian context. Future research should extend to investor behavior, transaction costs, and the regulatory role of OJK and DSN-MUI in shaping Islamic fintech.